2014
DOI: 10.4236/ojo.2014.43012
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Fracture of the Femur in Revision Total Hip Arthroplasty with a Fully HA-Coated Stem

Abstract: A retrospective review was made of intraoperative femoral fracture prevalence in seventy nine consecutive, cementless, fully HA-coated stems used for revision hip arthroplasty. Three patients were lost to follow up. Intraoperative fracture occurred in 15 (20%) femurs. Fractures occurred during cement removal (3/15) or insertion of the implant (12/15). All fractures were identified using intraoperative biplane X-ray, and were treated during the same operation. The clinical outcome of both groups (with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Concerning the complications, complication of eccentric reaming, femoral perforation and femoral fracture using extensively porous-coated femoral stem reported by Issack et al was 0.1%, 6 and the intraoperative fracture of femur in revision total hip arthroplasty with a fully hydroxyapatite-coated stem reported by Rothem et al was 20%. 12 Our study showed a higher intraoperative femur fracture of 27.9%. However, 25.6% of the intraoperative fracture occurred during removal of old implants and the cement (if any) which was not related to what type of new femoral stem used.…”
Section: Discussionmentioning
confidence: 45%
“…Concerning the complications, complication of eccentric reaming, femoral perforation and femoral fracture using extensively porous-coated femoral stem reported by Issack et al was 0.1%, 6 and the intraoperative fracture of femur in revision total hip arthroplasty with a fully hydroxyapatite-coated stem reported by Rothem et al was 20%. 12 Our study showed a higher intraoperative femur fracture of 27.9%. However, 25.6% of the intraoperative fracture occurred during removal of old implants and the cement (if any) which was not related to what type of new femoral stem used.…”
Section: Discussionmentioning
confidence: 45%